Pengaruh Variasi Diameter Pipa Primer Terhadap Pola Resapan Air Irigasi tetes Bertingkat Pada Media Tanam Polybag - Negara, I Dewa Gede Jaya; Hartana, Hartana; Supriyadi, Anid; Suroso, Agus; Julio, Ryan Bagus (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Multilevel drip irrigation is an irrigation method that supports water-saving agricultural activities in limited areas by channeling water through perforated pipes from emitters. The ideal multistage drip irrigation system can provide the same drip volume to plants, so the distribution of irrigation water and its depth need to be important factors to pay attention to in order to provide optimal plant irrigation. This research aims to determine the effect of using variations in primary channel pipe diameter on the distribution of drip irrigation and the depth of infiltration of irrigation products in a 3 (three) tier drip irrigation network. Tests were carried out on primary pipes from floors 1 to 3 with a diameter of ½", ¾" and pipes 1", with lateral drip pipes with ½" PVC. The size of the test field is 4 m x 1 m x 1.8 m and the distance between levels is around 0.9 m and the irrigation water source from a 200 liter tank is 2.5 m high. The research results showed that irrigation distribution results were quite good at all levels of the irrigation network, namely 70 ml and 68 ml. Irrigation patterns do not have a significant effect on the results of irrigation distribution due to variations in primary pipe diameter. A soil composition of 30% compost has achieved irrigation infiltration with a depth of 21 cm, including the fastest, namely 25 minutes and for 70% soil, an irrigation infiltration time of 35 minutes is required.